Biomedical and development paradigms in AIDS prevention - I. Wolffers (The World Health Organization, 2000)
In the fight against the HIV/AIDS pandemic different approaches can be distinguished, reflecting professional backgrounds, world views and political interests. One important distinction is between the biomedical and the development paradigms. The biomedical paradigm is characterized by individualization and the concept of ''risk''. This again is related to the concept of the market where health is a product of services and progress a series of new discoveries that can be marketed. The development paradigm is characterized by participation of the different stakeholders and by community work. The concept ''vulnerability'' is important in the development paradigm and emphasis is placed on efforts to decrease this vulnerability in a variety of sustainable ways. Biomedical technology is definitely one of the tools in these efforts. In the beginning of the pandemic the biomedical approach was important for the discovery of the virus and understanding its epidemiology. Later, stakeholders became involved. In the light of absence of treatment or vaccines, the development paradigm became more important and the two approaches were more in balance. However, since the reports about effective treatment of AIDS and hope of development of vaccines, the biomedical paradigm has become a leading principle in many HIV/AIDS prevention programmes. There is a need for a better balance between the two paradigms. Especially in developing countries, where it is not realistic to think that sustainable biomedical interventions can be organized on a short-term basis, it would be counterproductive to base our efforts to deal with HIV/AIDS exclusively on the biomedical approach.